2008
DOI: 10.3155/1047-3289.58.8.1086
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Assessment of Photochemical Modeling Systems in Air Quality Planning Applications

Abstract: The U.S. Environmental Protection Agency provides guidelines for demonstrating that future 8-hr ozone (O 3 ) design values will be at or below the National Ambient Air Quality Standards on the basis of the application of photochemical modeling systems to simulate the effect of emission reductions. These guidelines also require assessment of the model simulation against observations. In this study, we examined the link between the simulated relative responses to emission reductions and model performance as mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…The use of those ratios, referred as relative reduction factors (RRF), minimizes the effect of model-to-model variations in model pollutant predictions. Hogrefe et al (2008) demonstrate this point in a recent study, where they find marked model-tomodel differences in ozone concentrations of up to 20 ppb, but only minor differences in the relative response of ozone concentrations to emission reductions. As a result, even though different models can differ in the prediction of absolute pollutant concentrations, the resulting RRF would lead to similar relative responses to air pollution control strategies.…”
Section: Sensitivity Of Ozone Concentrations Due To Nitrogen Dioxide mentioning
confidence: 74%
“…The use of those ratios, referred as relative reduction factors (RRF), minimizes the effect of model-to-model variations in model pollutant predictions. Hogrefe et al (2008) demonstrate this point in a recent study, where they find marked model-tomodel differences in ozone concentrations of up to 20 ppb, but only minor differences in the relative response of ozone concentrations to emission reductions. As a result, even though different models can differ in the prediction of absolute pollutant concentrations, the resulting RRF would lead to similar relative responses to air pollution control strategies.…”
Section: Sensitivity Of Ozone Concentrations Due To Nitrogen Dioxide mentioning
confidence: 74%
“…Although never rigorously tested and reported in the science literature, the notion that chemical mechanism sensitivity relationships might hold over major urban areas over times scales of a decade or more never received serious investigation. Many studies have examined the ramifications of the EPA attainment equation [12][13][14] and its sensitivity to model inputs. No one has investigated the implication of applying the attainment equation in a place such as a Houston with its unique causes of O 3 violations.…”
Section: Technical Papermentioning
confidence: 99%
“…Although the differences in O 3 predicted by the two mechanisms can be large in an absolute sense, the importance of absolute concentrations is reduced in regulatory applications in which air quality models are used in a relative sense. For example, Hogrefe et al 41 showed that the relative response to emissions changes between the CMAQ model and the Comprehensive Air Quality Model with extensions (CAMx), when using the CB-IV chemical mechanism, were within a few ppb of each other although absolute model differences reached 20 ppb. To quantify model response to emission reductions, simulations utilizing the two mechanisms were made for three cases: a baseline, a 20% NO x reduction, and a 20% anthropogenic nonmethane VOC (NMVOC) reduction.…”
Section: Model Response To Emissions Changesmentioning
confidence: 99%